Single-cell protein production from purple non-sulphur bacteria-based wastewater treatment - Ojima Z. Wada (14155734) (2022)
Large-scale production of single-cell protein (SCP) has the potential not only to solve some of the food insecurity and water scarcity crises that plague a significant portion of our world today but also holds the promise to reduce the cost associated with the treatment of industrial and agricultural wastewater. Resource recovery of SCP from organic waste by microbes like yeast and microalgae is commonly documented. However, recently, a class of phototrophic bacteria, purple non-sulphur bacteria (PNSB), has emerged as a favourable option in terms of both wastewater treatment and resource recovery. PNSB are metabolically versatile and tolerant to a wide range of conditions, hence their ability to thrive in diverse waste streams. Besides its rich protein content, PNSB contains other nutritionally valuable bioproducts like carotenoids, coenzyme Q10, 5-aminolevulinic acid, and pantothenic acid. Recent evidence also indicates that PNSB-based aquafeed enhances growth and boosts immunity in certain aquaculture trials. It does not possess the same toxicity as most gram-negative bacteria due to its comparatively less potent lipopolysaccharide composition. With diverse promising prospects of PNSB-based SCP, it is critical to extensively examine the landscape from a holistic standpoint, highlighting the potential challenges large-scale SCP production may pose. Thus, this review explores the comparative advantages of utilizing PNSB for SCP production, essential components of PNSB-based SCP processing, and possible environmental and economic gains associated with the process. Current challenges with PNSB-based SCP production and future outlooks are also examined. Other Information Published in: Reviews in Environmental Science and Bio/Technology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s11157-022-09635-y